Performance Evaluation Of Image Processing Filters Towads Strawberry Leaf Disease (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The early identification of the plant leaf-disease is vital towards profitable harvest yield in the agri-field. Numerous researches have been carried out to detect the leaf disease on the agricultural land. specialists have done the plant distinguishing proof in India as plant supply oxygen for relaxing. there has been wide variety of disease has been presented on different plant.  The assurance of the infection on bacterial spot and yellow shading leaf is trying in the farming field.  The essential rationale is to distinguish the illness of the leaf as opposed to arranging it. The characterization of the infection requires huge target capacities to deal with it. In this work, the strawberry leaf disease of leaf spot, leaf scorch and leaf blight has been used as the input image. various noise filtering methods has been used to compare the best filter towards the leaf disease detection.  The experimental results on the proposed separating model has been assessed regarding PSNR and MSE incentive to clarify and demonstrate the precision of the sifting models utilized in this work.